AdBot robust advertisement recognition from TV and radio broadcast - Aniban, Aljon Rey P.; Cagadas, Emmanuel B.; Yap, Anna Mae C. (2010)
AdBot is a computerized advertisement monitoring system for TV and Radio broadcasts based on the Robust Landmark-Based Audio Fingerprinting algorithm. Landmarks are areas in an audio segment with high frequency concentration that are likely to survive even in the presence of noise or distortion. Each extracted landmark is converted into a hash value by using the start and end times and frequencies of the landmark. Advertisement stored in a database are represented by the landmarks extracted from them and the number of times these landmarks occured. The process of finding a match involves a database query to find the advertisement with the same landmarks. Once a sufficient number of matching landmarks have been found, a match is declared. Experiments involving advertisements corrupted with various levels of Additive White Gaussian Noise show that the system is robust against noise.
Thesis (B.S. Computer Science)-- University of the Philippines, Diliman
Keywords: Computerized advertisement monitoring system